Welcome to our community

Be a part of something great, join today!

On the Implication of Addition Axioms

OhMyMarkov

Member
Mar 5, 2012
83
Hello everyone!

I was trying to prove the propositions that follow the addition axioms as a revision, I got a different proof for the following proposition:

If $x+y=x+z$ then $y=z$

My proof was the following:
$x+y=x+z$, $(-x)+x+y=(-x)+x+z$, $0+y=0+z$, $y=z$

Rudin however, in his book, provides a different proof:
$y=0+y=(-x+x)+y=-x+(x+y)=-x+(x+z)=(-x+x)+z=0+z=z$

This is how I was thinking, I start from the condition, to reach the result. Is my proof incorrect?



Thanks!
 

Ackbach

Indicium Physicus
Staff member
Jan 26, 2012
4,197
I think both proofs are fine, so long as you can assume the following:

1. Existence and uniqueness of additive inverses
2. Existence and uniqueness of the additive identity
3. Associativity of addition
 

Evgeny.Makarov

Well-known member
MHB Math Scholar
Jan 30, 2012
2,502
It is not necessary to assume the uniqueness of additive inverses and the additive identity.

I agree that both proofs are correct and essentially the same. In some formal calculi, which identify proofs with simple variations, they may literally be the same proof.
 

Ackbach

Indicium Physicus
Staff member
Jan 26, 2012
4,197
It is not necessary to assume the uniqueness of additive inverses and the additive identity.

I agree that both proofs are correct and essentially the same. In some formal calculi, which identify proofs with simple variations, they may literally be the same proof.
Are you sure you don't need uniqueness of, say, the identity? I'm just wondering how
$$y=0+y=(-x+x)+y$$
would work if you didn't have uniqueness. How could you be sure that $-x+x=0$ and not $-x+x=0'$?
 

Evgeny.Makarov

Well-known member
MHB Math Scholar
Jan 30, 2012
2,502
The OP's proof does not use the uniqueness.

Are you sure you don't need uniqueness of, say, the identity? I'm just wondering how
$$y=0+y=(-x+x)+y$$
would work if you didn't have uniqueness. How could you be sure that $-x+x=0$ and not $-x+x=0'$?
You could use the 0 for which -x + x = 0. Then you rewrite y as 0 + y using that particular 0.